The perfect alibi [large type] - Margolin, Phillip (Margolin, Phillip. Robin Lockwood novels., 2019)
"A young woman accuses a prominent local college athlete of rape. Convicted on DNA evidence, the athlete swears his innocence. When a second rape occurs, DNA evidence again points to the imprisoned athlete. As young lawyer Robin Lockwood searches for answers, she finds herself enmeshed in a tangled web of buried secrets, lies, and violence"--